Comparison of Clinical Outcomes of Deceased Donor Kidney Transplantation according to Donor Evaluation Criteria. (August 2017) - Kang, Seong Sik; Park, Ha Yeon; Yeo, Sang Mok; Park, Woo Yeong; Han, Seungyeup; Park, Sung Bae; Yoon, Jeongsoo; Jin, Kyubok
Abstract : Introduction: Deceased donor kidney transplantation (DDKT) in Korea has been activated recently. However, discrepancies between needs and supply are still increasing, and the use of donors with acute kidney injury (AKI), expanded criteria (ECD), or high kidney donor profile index (KDPI) is also increasing. We investigated the clinical outcomes of DDKT in relation to AKI, ECD, and KDPI. Methods: We retrospectively analyzed DDKT performed at Keimyung University hospital between 2010 and 2014. Ninetyfour DD and their corresponding 95 KT recipients were included in this study. Results: The mean follow-up period was 42.6 ± 17.4 months (range 2‐81). Patients belonging to the AKI group were 42 (44.2%), ECD group were 23 (24.2%), and high KDPI (>85%) group were 16 (16.8%). The incidence of delayed graft function (DGF) was significantly higher in the AKI group than in the non-AKI group (P = 0.011), but not in the ECD group and the high KDPI group. The estimated glomerular filtration rate (eGFR) of the AKI group was significantly lower at 1 week, 2 weeks and 1 month after KT compared to the non-AKI group. After 3 months of KT, there was no significant difference in eGFR between the AKI group and non-AKI group, the ECD group and standard criteria donor group, and the high KDPI group and low KDPI group. Allograft survival rate showed no significant difference in the AKI, ECD, and high KDPI groups compared with the control groups. However, allograft survival rate was significantly lower only in the group with acute rejection (AR) than in the group without AR (P < 0.001). Patient survival rate showed no significant difference, according to donor AKI, ECD, or high KDPI. In multivariate analysis, AR was an independent risk factor for graft failure (hazard ratio 85.75, 95% confidence interval, 7.02-1047.77, P < 0.001), but AKI, ECD, or high KDPI were not. Conclusion: Donors with AKI showed significant association with incidence of DGF. However, kidneys with AKI, ECD, or high KDPI performed similarly to the control group in terms of graft function, graft survival, and patient survival. More detailed criteria for selecting a proper donor will be needed.